PLATFORMIZATION OF CONSPIRACISM: INTRODUCING A THEORETICAL FRAMEWORK FOR INVESTIGATING CONSPIRACY THEORIES ON "ALTERNATIVE" PLATFORMS USING A CASE STUDY OF BITCHUTE AND GAB - Mahl, Daniela; Zeng, Jing; Schäfer, Mike S. (AoIR Selected Papers of Internet Research, 2023)
Digital platforms have modified conspiracy theory communication as they enable users to publicly share their support, to circumvent traditional gatekeepers, and to form like-minded communities. However, the impacts of conspiracy discourses differ greatly between platforms. By drawing on critical platform studies, this article introduces a theoretical and analytical framework to investigate the interplay and mutual shaping between “alternative” platforms and conspiracy theory communication, which we describe as the _platformization of conspiracism_. Along the four interconnected dimensions of our framework – _infrastructure_, _economic model_, _governance_, and _user culture_ of platforms – we examine _BitChute_ and _Gab_ in the context of conspiracy theory communication. To investigate the platforms' technological features, business model, and governance practices, we conduct a documentation analysis of media reports and the platforms own news updates alongside an in-depth examination of each platform's functionality and interface. To gain insights into the user culture, i.e., the key characteristics and monetizing strategies of conspiracy theory propagators, we analyze 20 prominent conspiracy theory channels and profiles from BitChute and Gab, respectively. Findings from our study shed light on how both platforms have positioned themselves as technological equivalents to their “mainstream” counterparts by offering similar features and how they differ from their counterparts by presenting themselves as defenders of free speech. At the user level, our findings suggest that both platforms provide conspiracy propagators a fertile refuge through which they can maintain their presence and connection with their followers – which also allows them to profit from their visibility by receiving monetary rewards.